2010
DOI: 10.1080/17588920903548751
|View full text |Cite
|
Sign up to set email alerts
|

An early stage of conceptual combination: Superimposition of constituent concepts in left anterolateral temporal lobe

Abstract: Conceptual combination is an essential cognitive process, yet little is known about its neural correlates. In the present study, a categorization task was used to evoke patterns of neural activation for complex concepts (e.g., young man) as well as their constituents (e.g., young, man). A functional region of interest (fROI) within left anterolateral temporal lobe was identified as a possible site of conceptual combination. In this region, the superimposition of activity for constituent concepts reliably predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…These results have been replicated in both listening and reading (Bemis & Pylkkänen, 2013) as well as in production (Pylkkänen, Bemis, & Blanco Elorrieta, 2014), suggesting they are not modality-specific. Further, similar results have been obtained by Baron, Thompson-Schill, Weber, and Osherson (2010), Baron and Osherson (2011), who showed that the LATL is engaged in conceptual combination across and within words.…”
Section: Introductionsupporting
confidence: 85%
“…These results have been replicated in both listening and reading (Bemis & Pylkkänen, 2013) as well as in production (Pylkkänen, Bemis, & Blanco Elorrieta, 2014), suggesting they are not modality-specific. Further, similar results have been obtained by Baron, Thompson-Schill, Weber, and Osherson (2010), Baron and Osherson (2011), who showed that the LATL is engaged in conceptual combination across and within words.…”
Section: Introductionsupporting
confidence: 85%
“…Left ATL shows a similar response pattern, with increased activation to sentences compared to unintelligible speech (Spitsyna et al, 2006), and to stimuli of increasing semantic complexity (Humphries et al, 2006). These findings have led researchers to suggest that the left lateral prefrontal cortex and ATL are the locus of semantic unification (a process wherein multilexemic samples of language are bound into complex and coherent ideas; Hagoort et al, 2009) and of conceptual combination (Hickok and Poeppel, 2007;Baron et al, 2010).…”
mentioning
confidence: 72%
“…The anterior temporal lobes appear to be important for the process of conceptual combination. In a previous study (Baron et al, 2010) we showed that the neural representation of complex concepts (e.g., young man) in the left anterior temporal lobe is additive. Specifically, in that region, the representation of a complex concept can be predicted by the superimposition of the voxel-wise neural representations of its constituent concepts (e.g., young + man).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Many of these regions surround the left sylvian fissure (11)(12)(13)(14)(15)(16)(17)(18)(19), including regions of the inferior frontal cortex (13,14), inferior parietal lobe (12,20), much of the superior temporal sulcus and gyrus (12,15,21), and the anterior temporal lobes (17,20,22). Here, we describe two functional magnetic resonance imaging (fMRI) experiments aimed at understanding how the brain (in these regions or elsewhere) flexibly encodes the meanings of sentences involving an agent ("Who did it?…”
mentioning
confidence: 99%